2013
DOI: 10.1088/0004-637x/779/2/171
|View full text |Cite
|
Sign up to set email alerts
|

The Youngest Known X-Ray Binary: Circinus X-1 and Its Natal Supernova Remnant

Abstract: Because supernova remnants are short lived, studies of neutron star X-ray binaries within supernova remnants probe the earliest stages in the life of accreting neutron stars. However, such objects are exceedingly rare: none were known to exist in our Galaxy. We report the discovery of the natal supernova remnant of the accreting neutron star Circinus X-1, which places an upper limit of t < 4, 600 years on its age, making it the youngest known X-ray binary and a unique tool to study accretion, neutron star evol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 48 publications
6
72
0
Order By: Relevance
“…The distance to the source was recently determined from an X-ray light echo to be 9.4 +0.8 −1.0 kpc (Heinz et al 2015), a distance consistent with previous best estimates of around 8 kpc (see Heinz et al 2013 for a discussion of the various suggested distances to the source).…”
Section: Introductionsupporting
confidence: 82%
“…The distance to the source was recently determined from an X-ray light echo to be 9.4 +0.8 −1.0 kpc (Heinz et al 2015), a distance consistent with previous best estimates of around 8 kpc (see Heinz et al 2013 for a discussion of the various suggested distances to the source).…”
Section: Introductionsupporting
confidence: 82%
“…two systems are embedded in their natal supernova remnants, making them unusually young XRBs (a few ×10 3 yr for Circinus X-1 - Heinz et al 2013 and ∼ 2 × 10 4 yr for SS 433 -e.g. Goodall et al 2011).…”
Section: The Black Hole Jetmentioning
confidence: 99%
“…for SS 433 (Panferov & Fabrika 1997) and 3 × 10 35 -2 × 10 37 erg s −1 for Circinus X-1 (Sell et al 2010) but could be as high as ∼ 10 39 erg s −1 (based on what could be a protrusion of the jet on the south side of the supernova remnant; Heinz et al 2013). …”
Section: The Black Hole Jetmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that tides are more efficient than the ones in our model, by a factor of ≈ 3 when taking a non-rotating star. Alternatively, the observed orbital decay is either induced by the mass-transfer itself, or an additional spin-orbit coupling is responsible for it, as suggested by Heinz et al 2013. 6.3 Remarks on our results on the circularization timescale and their consequences (i) There is a variety of papers in the literature which base their description of the evolution of compact binaries on timescale considerations (see for example, Kalogera 1999, Yungelson et al 2006, Pylyser & Savonije 1988, Ma & Li 2009). Since citing all of them does not seem like a sensible choice, we rather show an example of how timescale considerations could fail.…”
Section: An Application To the Ns-hmxb Circinus X-1mentioning
confidence: 67%